2021
DOI: 10.1186/s40545-021-00343-6
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy preparedness in handling COVID-19 pandemic: a sharing experience from a Malaysian tertiary hospital

Abstract: This commentary shares the experience of a hospital pharmacy department in providing healthcare services during the COVID-19 outbreak in Malaysia. During this pandemic, the medication delivery system is redesigned to minimize contact among patients and the health care providers. Also, the remote medication monitoring system was implemented to deliver pharmaceutical care for inpatients. Communication technology was used to assist the pharmacist in medication counseling. QR codes to access videos demonstrating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 6 publications
(6 reference statements)
2
20
0
3
Order By: Relevance
“…Several researchers stress that using QR codes for curtailing the pandemic must be highly selective and not universal. Thong et al [ 77 ] and Cook et al [ 78 ] suppose that a QR code-based system may be used for telemedicine services only. Khan et al [ 79 ] argues that it may be functional only for needs of distant work to ensure uninterrupted processes.…”
Section: Resultsmentioning
confidence: 99%
“…Several researchers stress that using QR codes for curtailing the pandemic must be highly selective and not universal. Thong et al [ 77 ] and Cook et al [ 78 ] suppose that a QR code-based system may be used for telemedicine services only. Khan et al [ 79 ] argues that it may be functional only for needs of distant work to ensure uninterrupted processes.…”
Section: Resultsmentioning
confidence: 99%
“…Ward pharmacists work with other health professionals as a ward team to ensure each patient receives correct medication and to safeguard against medication errors when patients are admitted to, during hospitalisation, and discharged from hospital [13]. Even during the pandemic era, ward pharmacists have integrated several telehealth initiatives to communicate any pharmaceutical-related problems detected and to perform remote pharmaceutical care for COVID-19 patients [2]. When no ward pharmacists are stationed at the specialty wards, there remain screening and interventions by pharmacists when the e-prescriptions reach in-patient pharmacy.…”
Section: Discussionmentioning
confidence: 99%
“…In promoting rational evidence-based prescribing, prescriptions will be screened and reviewed by pharmacists before medications are dispensed [1,2]. Studies in different health care settings have found that up to 10% of prescriptions reviewed had problems that needed pharmacists' intervention [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our study did not compare the satisfaction level between VAS and TCS users, hence the satisfaction of existing TCS users especially among the elderly is unknown. The timing of data collection would affect the satisfaction of the users, [34] this survey was conducted during the pandemic in which the use of VAS could be a preferred option as it allowed the users to practice physical distancing [41] and this factor could have contributed to high satisfaction levels. Future research should consider assessing the satisfaction level of TCS users and the reasons of not selecting VAS in which the findings could be used as a reference for VAS improvement as well as the overall flow of outpatient dispensing activities.…”
Section: Discussionmentioning
confidence: 99%